Low-Frequency Pulsed Magnetic Field Improves Depression-Like Behaviors and Cognitive Impairments in Depressive Rats Mainly via Modulating Synaptic Function - Yang, Jiajia; Wang, Ling; Wang, Faqi; Tang, Xiaoxuan; Zhou, Peng; Liang, Rong; Zheng, Chenguang; Ming, Dong (Frontiers in Neuroscience, 2019)
Transcrainal magnetic stimulation (TMS) has shown great promise as a medical treatment of depression. The effectiveness of TMS treatment at high frequency has been well investigated, however, the low-frequency TMS in depression treatment has rarely been investigated in depression-induced cognitive deficits. Herein, this study was carried out to assess the possible modulatory role of low-frequency pulsed magnetic field (LFPMF) on reversing cognitive impairment in a model of depression induced by chronic unpredictable stress (CUS). Wistar rats were randomly allocated into four groups as follow: a control group (CON), a control applied with LFPMF (CON+LFPMF), a chronic unpredictable stress (CUS), and a CUS treated with LFPMF (CUS+LFPMF). During 8 weeks of CUS, comparing to those in CON group animals not only gained less weight, but also exhibited anhedonia, anxiety, and cognitive decline in behavioral tests. After two-week treatment of LFPMF, a 20mT, 1Hz magnetic stimulation, it reversed the impairment of spatial cognition as well as hippocampal synaptic function including long-term potentiation and related protein expression. Thus, LFPMF has shown effectively improvements on depressant behavior and cognitive dysfunction in CUS rats, possibly via regulating synaptic function.